AB0768 TREATMENT WITH TOFACITINIB IN REFRACTORY PSORIATIC ARTHRITIS. MULTICENTER STUDY OF 87 PATIENTS IN CLINICAL PRACTICE. (2nd June 2020) - Galindez, E.; Prieto-Peña, D.; Martín-Varillas, J. L.; Joven-Ibáñez, B.; Rusinovich, O.; Almodovar, R.; Alegre-Sancho, J. J.; Mendez Diaz, L.; Sellas-Fernández, A.; Martínez-Ferrer, À.; Garcia de Vicuna, R.; Ventín-Rodríguez, C.; et al.
Abstract : Background: Tofacitinib (TOFA) is the first JAKi approved for psoriatic arthritis (PsA) in Europe (July 2018). TOFA has shown efficacy in refractory patients to anti-TNF in Randomized Clinical Trials (RCT) ( Gladman D. NEJM 2017; 377: 1525-36 ). Objectives: To assess efficacy and safety of TOFA in clinical practice (CP). To compare the profile of CP with RCT Methods: Study of 87 patients of CP with PsA treated with TOFA; Results are expressed as percentage, mean±SD or median [IRQ]. Results: 87 patients (28♀/59♂), mean age of 52.8±11.4 years (Table 1). Pattern of joint involvement was: peripheral (n=60), axial (1) and mixed (26). Presented also enthesitis (49.4%), nail involvement (30.2%) and dactylitis (31%). Prior TOFA, most patients (80%) received oral prednisone, synthetic immunosuppressants (mean 2.3±0.9) and biological therapy (BT) (3.6±1.9): etanercept (n=58), adalimumab (54), infliximab (31), golimumab (37), certolizumab (30), secukinumab (54), ustekinumab (39) and ixekizumab (2). Apremilast was used in 17. After a mean follow-up of 12.3±9.3 years from PsA diagnosis, TOFA was started (5 mg/12 h). In 48 (55.2%) TOFA was used in combined therapy: methotrexate (30) and leflunomide (15). In the remaining 39, monotherapy was prescribed. Patients of CP compared with RCT have a longer duration of PsA, worst functional disability (HAQ) and received a higher proportion of corticosteroids and BT (anti-TNF and non-anti-TNF) (Table 1). Patients improved in activity indexes (PASI, DAS28, DAPSA) and laboratory test (table 2). Minor side effects were reported in 21 patients (gastrointestinal symptoms), and TOFA was discontinued in 29 due to inefficiency mainly. Conclusion: Patients of CP had a longer evolution and received a greater number of biologics than those of RCT. TOFA as in RCT seems effective, rapid and relatively safe for refractory PsA. Disclosure of Interests: E. Galindez: None declared, D. Prieto-Peña: None declared, José Luis Martín-Varillas Grant/research support from: AbbVie, Pfizer, Janssen and Celgene, Speakers bureau: Pfizer and Lilly, Beatriz Joven-Ibáñez Speakers bureau: Abbvie, Celgene, Janssen, Merck Sharp & Dohme, Novartis, Pfizer, Olga Rusinovich: None declared, RAQUEL ALMODOVAR Speakers bureau: Abbvie, Celgene, Janssen, Lilly, Novartis, Pfizer., Juanjo J Alegre-Sancho Consultant of: UCB, Roche, Sanofi, Boehringer, Celltrion, Paid instructor for: GSK, Speakers bureau: MSD, GSK, Lilly, Sanofi, Roche, UCB, Actelion, Pfizer, Abbvie, Novartis, LARA MENDEZ DIAZ: None declared, Agusti Sellas-Fernández Speakers bureau: Abbott, Lilly, Celgene, Pfizer, Schering-Plough, Janssen, Novartis, and Nordic Pharma, À Martínez-Ferrer: None declared, Rosario Garcia de Vicuna Grant/research support from: BMS, Lilly, MSD, Novartis, Roche, Consultant of: Abbvie, Biogen, BMS, Celltrion, Gebro, Lilly, Mylan, Pfizer, Sandoz, Sanofi, Paid instructor for: Lilly, Speakers bureau: BMS, Lilly, Pfizer, Sandoz, Sanofi, Clara Ventín-Rodríguez: None declared, Julio Ramirez: None declared, Manuel Moreno: None declared, Maria jose Moreno: None declared, María del Carmen Castro Villegas: None declared, Antia Crespo Golmar: None declared, Natalia Palmou-Fontana: None declared, FRANCISCO ORTIZ SANJUAN: None declared, Ximena Elizabeth Larco Rojas: None declared, Antonio Juan Mas: None declared, Christian Y Soleto: None declared, Iñigo Gorostiza: None declared, Miguel A González-Gay Grant/research support from: Pfizer, Abbvie, MSD, Speakers bureau: Pfizer, Abbvie, MSD, Ricardo Blanco Grant/research support from: AbbVie, MSD, and Roche, Speakers bureau: AbbVie, Pfizer, Roche, Bristol-Myers, Janssen, and MSD